Designing a Model of Socio-Economic Development of Iran – A Meta-synthesis Approach - Nahid Abdoli (پژوهش‌های برنامه و توسعه)
The concept of development can be studied from various points of view: from economic, social, cultural, and political standpoints to human, environmental, and sustainable perspectives. This study attempts to identify the pattern, indices, and variables of the economic and social development of Iran. The right to development emerges as the central concept of the constructive relationship between society and governance, so public awareness and participation in choosing a model, followed by legal guarantees and legal requirements for the realization of development in social life, are to be claimed and realized. Development is a right that is integral to fundamental human rights in the same spirit as freedom, justice, and equality. Using the meta-synthesis method, 44 patterns were obtained from 78 selected relevant articles published in the last five years. After stating the types of proposed models, the conservative social welfare model of Iran's social-economic development programs was explained and its relationship with macro policies was identified. The findings show that there is no sincere resolution to achieve sustainable and forward-looking goals, and management and planning compatible with the social and efficient structure have no place. As a result, development-oriented actions have been static, reactive, and inconstant which have led to a certain type of endogenous systemic conflict in the social structure.